Symbolic Public Goods and the Coordination of Collective Action: A Comparison of Local Development in India and Indonesia - Rao, Vijayendra (Washington, DC: World Bank, 2012)
Most economists think of common property as physical - a body of water, a forest - and as bounded within geographic space. In this paper, building on work in social theory, the author argues that common property can also be social-defined within symbolic space. People can be bound by well-defined symbolic agglomerations that have characteristics similar to common property. He calls these "symbolic public goods" (SPGs) and makes the case that such constructs are central to understanding collective action. He illustrates the point by contrasting how conceptions of nationalism in Indonesia and India created SPGs that resulted in very different strategies of local development. Indonesia emphasized collective action by the poor that resulted in a form of regressive taxation, enforced by the ideology of svadaya gotong royong (community self-help) that was both internalized and coercively enforced. India emphasized democratic decentralization through the panchayat system driven by the Gandhian ideology of gram swaraj (self-reliant villages). This has resulted in an unusual equity-efficiency tradeoff. Indonesia has delivered public services much more efficiently than India did, but at the cost of democratic freedoms and voice. The author argues that the challenge for these countries is not to undermine their existing SPGs but to build on them. Indonesia should retain the spirit of svadaya gotong royong but channel it in an equitable and democratic direction, while India should build the capacity of the panchayat system by giving it fiscal teeth, while promoting underutilized institutions such as Gram Sabhas (village meetings) that encourage accountability and transparency.